Images for a peaceful planet ([Ottawa] NFBC)
Presents quarrels among neighbors, wars, nuclear desolation and the damages these bring to society.
1. Balablok -- 2. Neighbors -- 3. Children of war -- 4. No more Hiroshima -- 5. A writer in the nuclear age -- 6. If you love this planet -- 7. The Big snit.
VHS
Keywords: Peace -- Societies, etc; Animation; Sociology